162 A REVIEW OF THE GENERAL PRACTITIONER REFERRALS TO A RAPID ACCESS FRAILTY ASSESSMENT UNIT IN A MODEL-3 HOSPITAL. (25th October 2022) - Kitic, DB; Ibrahim, M; McGlynn, J; O'Keane, C; Donnelly, T; Kemple, O
Abstract: Background: The Rapid Access Frailty assessment unit (RAFAU) was set up in February 2021 and is run by a Raft (Rapid access frailty team). This is a dedicated multidisciplinary team in a model three hospital to review frail older patients to improve outcomes and admission avoidance. They review patients in the Emergency department as well as the assessment unit and on the ward for inpatient frailty reviews. The team is expanding as new roles are incorporated into the team and our service has evolved into a five day a week rapid access service. Methods: We examined the number of GP referrals to our RAFU since May 2021 to March 2022 and the outcome of the review. Data was collected on all patients attending the RAFAU over an 11-month period. We selected all GP referrals which produced a cohort of 259 referrals to the unit. Results: A total of 259 referrals were reviewed in RAFAU clinics. Mean age was 70-75 years old 60% were female, 40 % male. Reason for referral included: 38 % medical reasons, 32% cognitive issues, 18 % mobility, 7 % falls. Overall, 41% of referred patients had Clinical frailty scale score of 1-3, 16 % had a clinical frailty scale of 4, 8% clinical frailty scale of 5, 9% clinical frailty scale of 6, 5% clinical frailty scale of 7.The outcome of this cohort were as follows: 86 % needed further follow up, 9% were discharged and 1% admitted. Conclusion: The RAFAU gives an alternative referral destination to GP's for rapid review of frail older patients and thus potentially avoiding ED referral and admission. The vast majority of these referrals were for review of medical issues and cognitive assessment. The majority of patients required ongoing specialist frailty services and we hope to expand our service in the future.